The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1118/1.3284539
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different computed radiography systems: Physical characterization and contrast detail analysis

Abstract: This study suggests that systems based on the dual-side reading or line-scanning reading with columnar phosphors provide a remarkable improvement when compared to conventional CR units and yield results in line with those obtained from most digital detectors for radiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 28 publications
(34 reference statements)
1
19
0
2
Order By: Relevance
“…15, we plotted three CD curves: one coming from experimental data for the AcSelerate system (RQA5 at 2.5 lGy), one theoretical curve calculated with the Rose model, and finally one of the best curve for other systems gathered from recent published data. 14 The CD response of the AcSelerate is in line with the best published data. Figure 16 shows a comparison of the CD curves estimated by human observers for images acquired with the RQA5 beam at an exposure of about 2.5 lGy with and without the CRF filter.…”
Section: Iiib Contrast-detail Analysissupporting
confidence: 87%
See 1 more Smart Citation
“…15, we plotted three CD curves: one coming from experimental data for the AcSelerate system (RQA5 at 2.5 lGy), one theoretical curve calculated with the Rose model, and finally one of the best curve for other systems gathered from recent published data. 14 The CD response of the AcSelerate is in line with the best published data. Figure 16 shows a comparison of the CD curves estimated by human observers for images acquired with the RQA5 beam at an exposure of about 2.5 lGy with and without the CRF filter.…”
Section: Iiib Contrast-detail Analysissupporting
confidence: 87%
“…Note that, like most of the systems manufactured by FUJI-FILM, the system presents a logarithmic behavior for all four beams. 13,14 All the subsequent measurements (both physical and psychophysical characterization) were then performed on linearized images.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies [2][3][4][5][6][7][8][9][10][11][12] have reported largely standardized methods to measure the physical performance of imaging systems based on the International Electrotechnical Commission IEC 62220-1 standard. 4 These studies were based on the metric-the detective quantum efficiency (DQE)-which reflects detector efficiency when forming an image using a limited number of x-ray photons, providing an input signalto-noise ratio (SNR) at a specific exposure level.…”
Section: Introductionmentioning
confidence: 99%
“…The results of our preliminary investigation using a mammographic computed radiography (CR) system, based on photostimulable granular phosphors and dual-side reading [20], demonstrated good results in both contrast and spatial resolution [2]. A single photon counting detector has been designed for mammography at the SYRMEP beamline and is now under commissioning.…”
Section: Discussionmentioning
confidence: 99%